Humid atmospheric pressure plasma jets exposed micro-defects on CoMoO4 nanosheets with enhanced OER performance. Issue 64 (22nd July 2019) - Jiang, Haishun; Cui, Zhe; Xu, Chaoting; Li, Wenyao
Abstract : A novel humid APPJs method was adopted to treat CoMoO4 nanosheet arrays resulting in micro-defects and more reaction intermediates that led to an enhanced OER property. Abstract : Humid atmospheric pressure plasma jets (APPJs) sustained in an argon/water vapour mixture were adopted to treat CoMoO4 nanosheets arrays, which resulted in micro-defects on the surface and the appearance of hydroxyl (OH − ) groups absorbed on the nanosheets. Benefiting from these changes, the plasma treated CoMoO4 exhibited similar catalytic property to RuO2, an overpotential 70 mV lower than for pristine CoMoO4 and maintained good stability after 30 hours for the water oxidation.